A novel multicopy suppressor of a groEL mutation includes two nested open reading frames transcribed from different promoters. - Greener, T (1993)
When present on a multicopy plasmid, a newly discovered gene (sugE) mapping to 94 min on the Escherichia coli chromosome, suppresses a groEL mutation and mimics the effects of groE overexpression. A groEL mutant of E.coli, transformed with the Klebsiella pneumoniae nif gene cluster, failed to accumulate nitrogenase components [Govezensky et al. (1991) J. Bacteriol., 173, 6339-6346]. Transformation with sugE reversed the mutant phenotype. In wild type K.pneumoniae, transformation with sugE accelerated the rate of nitrogenase biogenesis after nif derepression. In E.coli, transformation with sugE enabled bacteriophage T4 growth in a groEL mutant. A continuous 178 codon open reading frame (ORF) in sugE encloses another, in-frame, 105 codon ORF similar to a predicted ORF in Proteus vulgaris. In vivo products of both sugE ORFs were observed in transformants expressing the gene from a T7 promoter. In non-transformed cells, a typical sigma 70-dependent promoter found upstream of the larger ORF directs sugE transcription during growth at 30 degrees C. At elevated temperatures or in stationary phase cells, another promoter, found within the coding sequence upstream of the smaller ORF, is activated independently of sigma 32. The results suggest that sugE encodes a chaperonin-related system whose composition might vary with temperature and growth phase.